Elucidating Common Structural Features of Human Pathogenic Variations Using Large‐Scale Atomic‐Resolution Protein Networks. Issue 5 (7th April 2014) - Das, Jishnu; Lee, Hao Ran; Sagar, Adithya; Fragoza, Robert; Liang, Jin; Wei, Xiaomu; Wang, Xiujuan; Mort, Matthew; Stenson, Peter D.; Cooper, David N.; Yu, Haiyuan
<x xml:space="preserve">Abstract</x> We combine the scale of network systems biology with the resolution of traditional structural biology to generate a large‐scale atomic‐resolution interactome‐network comprising 3, 398 interactions between 2, 890 proteins with a well‐defined interaction interface and interface residues for each interaction. Using this atomic‐resolution network, we elucidate key structural principles underlying variations causing human inherited disease. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>